Address Forms in Minangkabau Language at Pariaman Region of West Sumatera in Indonesia - Sevrika, Hevriani (TELL - US JOURNAL, 2016)
This article aims to describe form of using address form based on matrilineal progeny in minangkabauneese in Pariaman region, to describe form based on marriage in Minangkabauneese in Pariaman region, and to describe about the address form is given based on the differences of physically appearance and the orderly position in the family kinship in Pariaman region. This research is qualitative research by using descriptive method. The research data is address form in Minangkabauneese in Pariaman region sub – district Pariaman. The source of this research is verbal source as a primary source uttered by informant as native speaker. The data is collected by using listening method, recording technique and writing technique as continuation technique. The research findings are there are 10 address form for grandparents, 12 address form for parents, 33 address form of brothers or sisters from mother,  21 address form of brothers or sisters from father, and 24 address form of older brothers or sisters in Pariaman region.